Co‐combustion and ash characteristics of Zhundong coal with rice husk hydrochar prepared by the hydrothermal carbonization technology for co‐combustion. Issue 2 (7th December 2021) - Yang, Li; Wang, Hui; Zhu, Jingwen; Sun, Wei; Xu, Youning; Wu, Shaohua
Abstract: The high content of the AAEMs in Zhundong (ZD) coal causes easily slagging on the heating surface of boilers, and the addition of rice husk hydrochar (RHC) is expected to alleviate slagging by introducing SiO2 content. ZD coal is co‐fired with RHC according to different blend ratios, co‐combustion ashes are prepared subsequently at different temperatures. The co‐combustion characteristics of blends are studied firstly by using TGA, considering the combustion process can bring impacts on ash characteristics. Then the effects of the blend ratio and ashing temperature on the ash characteristics are discussed. The ash samples are characterized by XRF, ICP‐AES, XRD and SEM. The results show that an increase in the blend ratio of the RHC reduces the ignition temperature and lengthens the burnout time, which transforms the ash characteristics. The contents of quartz, gehlenite and andalusite greatly increase. The number of fine particles in the ash decreases, while the particle size increases. The ash fusion temperatures (AFTs) are at the lowest value at 8:2 and exceed totally that of ZD coal at 7:3. Considering to increase the AFTs of ZD coal, at least the blend ratio of 7:3 of ZD coal and RHC is recommended for co‐combustion.